VISSIM Modeling and Simulation to Optimize the Performance of the Blimbing Ngoro Three-Way Intersection in Jombang Regency - Saputri, Firda Auliya Ajie; Patriadi, Andi; Tjendani, Hanie Teki (INTERNATIONAL JOURNAL ON ADVANCED TECHNOLOGY, ENGINEERING, AND INFORMATION SYSTEM, 2025)
This research aims to analyze the existing conditions of the intersection and provide performance improvement solutions through modeling and simulation using PTV VISSIM software. Data was obtained through field surveys, interviews with stakeholders, and related literature studies. The analysis was conducted with reference to the Indonesian Road Capacity Guidelines (PKJI) 2023 to measure performance parameters such as degree of saturation, queue length, and average delay. The results showed that the existing condition of the Blimbing Three Intersection was at the LOS D level of service, with an average delay of 30.99 seconds and a queue length of 26.53 meters, reflecting less than optimal traffic performance. Based on the ARRB analysis, it is necessary to control the intersection by installing traffic signals to improve safety and efficiency. Three proposed scenarios were tested using VISSIM simulation, where Proposal 1 produced the best performance with a delay of 20.34 seconds and a queue of 10.37 meters (LOS C). Proposal 2, with a three-phase arrangement, actually worsened conditions with a delay of 54.72 seconds and a queue of 84.44 meters (LOS D). Meanwhile, Proposal 3, which combines three phases and the left-turn on-ramp feature (LTOR), gives almost as good results as Proposal 1, with a delay of 24.05 seconds and a queue of 16.28 meters, remaining at LOS C. Therefore, Proposal 3 is considered the most effective solution as it is able to improve traffic flow without neglecting the safety aspect.